PENGGUNAAN BAHASA INDONESIA DI DAERAH DANAU KUBRA - ESTER MEISY TARIGAN; ELSA NORA SARAGIH (JURNAL ILMIAH KOHESI, 2022)
Research on the use of Indonesian has been widely done by researchers either in the use in the learning process or also inthe use of Indonesian in the midst of society. But research on the use of Indonesian in tourist attractions is still rare.Therefore, this study tried to reveal how the use of Indonesian in the tourist attractions of Lake Kubra. This research methoduses a qualitative approach, with data collection methods with interviews and obserbation. Researchers act as participantobservers who jump directly to observe the residents and tourists who visit Lake Kubra. The results showed that residentsaround Lake Kubra and local tourists visiting Lake Kubra used Javanese in their interactions, tourists and tour providersaround Lake Kubra. It is hoped that more research on the use of Indonesian in other tourist attractions can be done to seehow the use of Indonesian in tourist areas. So that stakeholders can socialize the use of Indonesian in tourist attractions, sothat communication between visitors and tourist providers can run smoothly, there is no misunderstanding.